Drug-eluting beads transarterial chemoembolization vs conventional transarterial chemoembolization in the treatment of hepatocellular carcinoma in adult patients: a systematic review and update meta-analysis of observational studies - Chernyshenko, Tatiana; Polkin, Roman; Dvoinikova, Ekaterina; Shepelev, Valeriy; Goncharuk, Roman (Frontiers in Oncology, 2025)
Study designSystematic review and update meta-analysis.PurposeThe present systematic review and meta-analysis were conducted to compare the efficacy and safety of the two approaches for HCC in adult patients (DEB-TACE vs cTACE).Overview of literatureThe TACE procedure is indicated for the treatment of HCC with intermediate (BCLC B) and early (BCLC A). Conflicting data obtained from earlier meta-analyses comparing DEB-TACE with cTACE prompted the updated meta-analysis.MethodsThe study included adult patients over the age of 18 with HCC. MEDLINE conducted a literature search using Pubmed and Google Scholar up to May 2024. The following parameters were evaluated: the effectiveness of the tumor response to treatment according to the mRECIST criteria (CR, PR, SD, PD), overall survival, progression-free survival, and complication rate. 32 retro- and prospective studies were analyzed.ResultsThe study included 4,367 patients. The radiological response of the tumor in all four CR, PR, SD, and PD parameters in the DEB-TACE group showed the best response. The overall survival rate during the DEB-TACE procedure was higher by 3.54 months (p <0.00001), and progression-free survival (PFS) by 3.07 months (p <0.0001), respectively. The incidence of complications was comparable in both groups.ConclusionsThe results of the meta-analysis revealed clinically significant advantages of DEB-TACE in comparison with cTACE. Being comparable in terms of the frequency of complications, DEB-TACE demonstrated the best result in the radiological response of the tumor to the therapy, in terms of overall survival and progression-free survival.